2020
DOI: 10.1021/acs.est.0c02259
|View full text |Cite
|
Sign up to set email alerts
|

High Anthropogenic Organic Matter Inputs during a Festival Increase River Heterotrophy and Refractory Carbon Load

Abstract: Streams and rivers metabolize dissolved organic matter (DOM). Although most DOM compounds originate from natural sources, recreational use of rivers increasingly introduces chemically distinct anthropogenic DOM. So far, the ecological impact of this DOM source is not well understood. Here, we show that a large music festival held adjacent to the Traisen River in Austria increased the river’s dissolved organic carbon (DOC) concentration from 1.6 to 2.1 mg L –1 and stream ecosystem respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 69 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…There is a growing body of evidence that anthropogenic trace contaminants, and contaminants of emerging concern (CECs), such as pharmaceuticals, herbicides, and antimicrobial agents can have major impacts upon the composition and functioning of aquatic microbial communities (Rosi-Marshall et al 2013;Argudo et al 2020;Harjung et al 2020;McClean and Hunter 2020;Ke et al 2020;Kusi et al 2020). Exposure to contaminants such as the antibacterial agent Triclosan (Hay et al 2001;Drury et al 2013) and the herbicide Diuron (Sumpono et al 2003;Seghers et al 2003) has been observed to place microbial communities under a selective pressure that favors microorganisms that can use these contaminants as an additional carbon source.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence that anthropogenic trace contaminants, and contaminants of emerging concern (CECs), such as pharmaceuticals, herbicides, and antimicrobial agents can have major impacts upon the composition and functioning of aquatic microbial communities (Rosi-Marshall et al 2013;Argudo et al 2020;Harjung et al 2020;McClean and Hunter 2020;Ke et al 2020;Kusi et al 2020). Exposure to contaminants such as the antibacterial agent Triclosan (Hay et al 2001;Drury et al 2013) and the herbicide Diuron (Sumpono et al 2003;Seghers et al 2003) has been observed to place microbial communities under a selective pressure that favors microorganisms that can use these contaminants as an additional carbon source.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we explored the usefulness of DOM quality indices derived from fluorescence spectroscopy as promising additional parameters to be included in the D-A-(C) index. Fluorescence spectroscopy of DOM has previously been used mainly to examine shifts in DOM composition in surface water systems with season, changing environmental conditions, or in response to anthropogenic impacts, (Benk et al 2019;Coble et al 2014;Harjung et al 2020). Moreover, it has been used to study risks of fecal contamination in groundwater and drinking water systems (Frank et al 2018;Nowicki et al 2019;Sorensen et al , 2020.…”
Section: Originalarbeitmentioning
confidence: 99%
“…There is a growing body of evidence that anthropogenic trace contaminants, and contaminants of emerging concern (CECs), such as pharmaceuticals, herbicides, and antimicrobial agents can have major impacts upon the composition and functioning of aquatic microbial communities (Rosi-Marshall et al 2013;Argudo et al 2020;Harjung et al 2020;McClean and Hunter 2020;Ke et al 2020;Kusi et al 2020). Exposure to contaminants such as the antibacterial agent Triclosan (Hay et al 2001;Drury et al 2013) and the herbicide Diuron (Sumpono et al 2003;Seghers et al 2003) have been observed to place microbial communities under a selective pressure that favors microorganisms that can use these contaminants as an additional carbon source.…”
Section: Introductionmentioning
confidence: 99%